Posted by **NGOFAKA** on Tuesday, October 23, 2007 at 11:49am.

if sqrt(y)=(arctan)tan-1(x), show that (1+x^2)dy/dx((1+x^2)dy/dx)=2

## Answer This Question

## Related Questions

- Pre Cal. - Evaluate tan(cos^(-1)(3/2 )+tan^(-1)(3/3))? arccos(sqrt(3) / 2...
- Calculus - Pls help solve this problem if sqrt(y)=(arctan)tan-1(x), show that (1...
- Maths - if sqrt(y)=arctan(x), show that (1+x^2)dy/dx((1+x^2)dy/dx)=2
- calculus - Now we prove Machin's formula using the tangent addition formula: tan...
- limiting position of the particle - A particle moves along the x axis so that ...
- calc - also: integral of tan^(-1)y dy how is integration of parts used in that? ...
- check my arctan please - arctan(1/12)= 4.763 rounded to the nearest tenth degree...
- calculus - Let f be a function defined by f(x)= arctan x/2 + arctan x. the value...
- trigonometry - tan60=2 tan30/1-tan^2 30 sqrt(3)=I'm confused of that 2 but i ...
- calculus - can anyone tell me if tan-1x= 1 over tan x? No. They are different. ...

More Related Questions